Respuesta :
Answer:
y=2 x=2
Step-by-step explanation:
x = -2y + 6
3•(-2y+6) - y = 4
- 7y = -14
7y = 14
y = 2
x = -2y+6
y = 2
x = -2(2)+6 = 2
x=2
Step-by-step explanation:
solve for y in both equations
- 3x-y=4
subtract 3x from both sides
-y=4-3x
multiply the equation by -1
y=-1(4-3x)
- 2y+x=6
subtract both sides by x
2y=6-x
divide both sides by 2
y=(6-x)/2
- Now set the y values equal to each other
-1(3x-4)=(6-x)/2
-3x+4=(6-x)/2
multiply both sides by 2
-6x+8=6-x
add 6x to both sides and subtract 6 to both sides
2=x
put 2 back into x for y=(6-x)/2
y=2
Hope that helps :)